Association Between AGT M235T and Left Ventricular Mass in Vietnamese Patients Diagnosed With Essential Hypertension - Tran, Tuan Thanh; Mai, Thao Phuong; Tran, Ha Chau Bich; Le, Linh Hoang Gia; Vu, Hoang Anh; Tran, Trang Kim; Hoang, Sy Van; Chau, Hoa Ngoc; Do, Minh Duc (Frontiers in Cardiovascular Medicine, 2021)
Background: Increasing left ventricular mass in hypertensive patients is an independent prognostic marker for adverse cardiovascular outcomes. Genetic factors have been shown to critically affect left ventricular mass. AGT M235T is one of the genetic polymorphisms that may influence left ventricular mass due to its pivotal role in the regulation of plasma angiotensinogen level as well as hypertension pathophysiology in Asian populations. Currently, how M235T affects left ventricular mass is not well-described in Vietnamese hypertensive patients. This study aimed to investigate the association between M235T and left ventricular mass in Vietnamese patients diagnosed with essential hypertension. Materials and methods: AGT M235T genotyping and 2D echocardiography were performed on 187 Vietnamese subjects with essential hypertension. All the ultrasound parameters were obtained to calculate the left ventricular mass index according to the American Society of Echocardiography and the European Association of Cardiovascular Imaging 2015 guidelines. Other clinical characteristics were also recorded, including age, gender, duration of hypertension, hypertensive treatment, lifestyle, renal function, fasting plasma glucose, and lipid profile. Results: MT and TT genotypes were determined in 30 and 157 subjects, respectively. AGT M235T genotype, duration of hypertension, body mass index, and ejection fraction statistically affected the left ventricular mass index, which was significantly greater in TT compared to MT carriers after adjusting for confounding factors. Conclusion: The TT genotype of AGT M23T was associated with greater left ventricular mass in Vietnamese patients diagnosed with essential hypertension.